Factors influencing non-compliance to family planning practice among high-risk women in Negeri Sembilan / Erlly Kasmuni and Noraini Hashim - Kasmuni, Erlly; Hashim, Noraini (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Family planning program is essential as s a vital indicator for tracking progress on improving maternal health. Ministry of Health stated family planning is one of four pillars Safe Motherhood Initiative with antenatal care, safe delivery and postnatal care. This study identifies factors influencing noncompliance to family planning practice among high-risk women in Negeri Sembilan. A cross- sectional study was conducted among women categorised under high-risk at 28 Health Clinic in Negeri Sembilan from February until April 2020. High-risk women who participated using stratified sampling (n=309) were ask to complete a self-administer questionnaire. Data were analysed using IBM-SPSS Statistics Version 25. The main reason for non-compliance was forgotten to take the chosen method on time 112 (36.2%) and followed by fear of side effects of methods 95 (30.7%). Knowledge levels about family planning of the participant were approximately the same between good knowledge 123 (39.8%) and poor knowledge 122 (39.5%). The respondents showed a satisfactory attitude towards family planning practices 202 (65.4%). There was a statistically significant association between level of knowledge and attitude toward family planning practise (p<0.05). In conclusion, individual behaviour is the main contributor to non-compliance to family planning practice among high-risk women